Benchmarking GATE/Geant4 for 16O ion beam therapy. (5th September 2017) - Resch, Andreas F; Fuchs, Hermann; Georg, Dietmar
Abstract: Oxygen ( 16 O ) ions are a potential alternative to carbon ions in ion beam therapy. Their enhanced linear energy transfer indicates a higher relative biological effectiveness and a reduced oxygen enhancement ratio. Due to the limited availability of 16 O ion beams, Monte Carlo (MC) transport codes are important research tools for investigating their potential. The purpose of this study was to validate GATE/Geant4 for 16 O ion beam therapy using experimental data from literature. Five hadron physics lists and two electromagnetic options were benchmarked against measured depth dose distributions (DDDs) and charge-changing cross sections. The simulated beam ranges deviated by less than 0.5% for all physics configurations and only a few points exceeded the gamma index criterion (2%/1 mm). However, the simulated partial charge-changing cross sections deviated considerably for some hadron physics configurations. Best agreement with the experimental values was obtained with the quantum molecular dynamics model (QMD), and we therefore suggest using this model in Geant4 to accurately describe the fragmentation of 16 O ion beams into lighter fragments ( 5 ⩽ Z ⩽ 7 ).